2020
DOI: 10.1016/j.celrep.2020.107766
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cellular Response to Translocated Toxic Effectors and Physical Penetration by the Type VI Secretion System

Abstract: Highlights d Combinatorial effector inactivation delineates functions and physical contact d Tit-for-tat of P. aeruginosa responds to a specific effector TseL d Immunity-independent stress responses provide protection against TseL toxicity d Stress response is akin to microbial innate immunity for general protection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 60 publications
3
79
0
Order By: Relevance
“…Most recently, an elegant study by Kamal et al (55) showed that a single effector of V. cholerae (TseL) was necessary and sufficient for generating activation of the H1-T6SS of P. aeruginosa through the classical tit-for-tat interaction with T6SS + V. cholerae. Ectopic expression of tseL in the periplasm of P. aeruginosa (but not in the cytosol) could also trigger T6SS assembly in a TagQRST-dependent fashion (55). Given that TseL is a lipase and that lipases are very common effectors of T6SSs (8,94,95), it is possible that a signal generated by phospholipid hydrolysis within the periplasm is recognized by part of the P. aeruginosa TagQRST sensory transduction system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, an elegant study by Kamal et al (55) showed that a single effector of V. cholerae (TseL) was necessary and sufficient for generating activation of the H1-T6SS of P. aeruginosa through the classical tit-for-tat interaction with T6SS + V. cholerae. Ectopic expression of tseL in the periplasm of P. aeruginosa (but not in the cytosol) could also trigger T6SS assembly in a TagQRST-dependent fashion (55). Given that TseL is a lipase and that lipases are very common effectors of T6SSs (8,94,95), it is possible that a signal generated by phospholipid hydrolysis within the periplasm is recognized by part of the P. aeruginosa TagQRST sensory transduction system.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical substances that interact with gram-negative lipopolysaccharides (LPSs), including polymyxin B (43), DNA, and chelators (54), can also activate the H1-T6SS of P. aeruginosa (again dependent on the TagQRST-PpkA-FhA1-PppA system) and these outer membrane perturbants can trigger rapid (i.e., under 1 min) assembly and firing of the H1-T6SS apparatus. Finally, the V. cholerae lipase TseL (47) has been reported to be necessary and sufficient to induce the tit-for-tat response by P. aeruginosa (55), suggesting that enzymic attack of membrane phospholipids may also trigger the TagQRST-PpkA-FhA1-PppA pathway of H1-T6SS assembly and firing.…”
Section: Significancementioning
confidence: 99%
“…Although the molecular regulation of retaliatory T6SS firing has received attention 27 , 28 , 30 , 34 , its evolution has not—leaving open the question of why such a complex strategy has evolved in bacteria, and only in some species. At a broader level, while the evolution of reciprocation has a long history of study in evolutionary biology 35 38 , past efforts have focused largely on the evolution of reciprocal cooperation, rather than competition.…”
Section: Introductionmentioning
confidence: 99%
“…So far, it has been shown that various stimuli can trigger counterattacks in P. aeruginosa strain PAO1, including incoming T6SS attacks from multiple bacterial species 23,27,28 , conjugative T4SS pili 29 , and membrane-disrupting antibiotics like polymyxin B 29 . There is also evidence that retaliation can be toxin-specific-not all T6SS effectors trigger counterattacks, and in V. cholerae, only the lipase effector TseL triggers retaliation 30 . Across stimuli, P. aeruginosa appears to be responding to membrane perturbation, and a putative model is that this response is mediated post-transcriptionally via the TagQRST pathway.…”
mentioning
confidence: 99%
“…Membrane damage from an incoming conjugative pilus or polymyxin B can likewise trigger this response [7]. A specific toxin effector from a competitor T6SS has also been shown to activate the T6SS [8] in a manner reminiscent of colicin activation by the SOS response following colicin-mediated DNA damage (Fig 1). Additional signals from quorum sensing and nutrient availability are also integrated into these control mechanisms [9].…”
mentioning
confidence: 99%